1200 EFFECT OF BALANCE TRAINING AFTER HIP FRACTURE SURGERY: A SYSTEMATIC REVIEW OF RANDOMISED CONTROLLED STUDIES. (16th January 2023) - Moniati, F; Costa, C; Chatzimatthaiou, C; Chatzimatthaiou, M
Abstract: Introduction: Hip Fracture Surgery (HFS) can result in balance impairment which is associated with an increased risk of falls in the elderly as well as limitations in their mobility. Balanced Training (BT) is a rehabilitation method used aiming to minimize the balance impairments post HFS. BT options include stepping, balance task-specific exercise, standing on one leg, yoga. Our main outcome is to evaluate the effect of BT on the physical functioning of elderly patients post an HFS. Methods: We conducted a systematic review using the PubMed-Medline, Cochrane Library and Embase databases to locate randomized controlled trials which compared BT with standard care post HFS. The Cochrane' Library Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was used as our template for the review. Results: Overall, nine randomised controlled trials were selected, comprising a total of 712 patients, all aged 65 years of age and older. With regards to the type of BT rehabilitation: four trials used step-ups (n=500), three trials used balance task-specific exercise (n=170) and two studies used standing on one leg (n=42). The BT group demonstrated improvement in physical functioning post HFS compared to the control group (Standardised Mean Difference (SMD) = 0.410). Moreover, all functional parameters which include, lower limb strength, performance task and health related quality of life, were also improved in the BT group. Conclusion: Evidently, the results demonstrate an improvement of physical functioning by BT post HFS. Furthermore, the positive effects on all functioning parameters were apparent. As a result, the implementation of BT in postoperative rehabilitation programs in elderly patients with hip fractures should be considered. Reference: [1] Monticone M, Ambrosini E, Brunati R, et al. How balance task-specific training contributes to improving physical function in older subjects undergoing rehabilitation following hip fracture: a randomized controlled trial. Clin Rehabil. 2018;32:340–351.